A phase Ib trial of combined PKC and MEK inhibition with sotrastaurin and binimetinib in patients with metastatic uveal melanoma - Bauer, Sebastian; Larkin, James; Hodi, F. Stephen; Stephen, Frank; Kapiteijn, Ellen H. W.; Schwartz, Gary K.; Calvo, Emilano; Yerramilli-Rao, Padmaja; Piperno-Neumann, Sophie; Carvajal, Richard D. (Frontiers in Oncology, 2023)
Background: Uveal melanoma is a disease characterized by constitutive activation of the G alpha pathway and downstream signaling of protein kinase C (PKC) and the mitogen-activated protein kinase (MAPK) pathway. While limited clinical activity has been observed in patients with metastatic disease with inhibition of PKC or MEK alone, preclinical data has demonstrated synergistic antitumor effects with concurrent inhibition of PKC and MEK. Method: We conducted a phase Ib study of the PKC inhibitor sotrastaurin in combination with the MEK inhibitor binimetinib in patients with metastatic uveal melanoma using a Bayesian logistic regression model guided by the escalation with overdose control principle (NCT01801358). Serial blood samples and paired tumor samples were collected for pharmacokinetic (PK) and pharmacodynamic analysis. Results: Thirty-eight patients were treated across six dose levels. Eleven patients experienced DLTs across the five highest dose levels tested, most commonly including vomiting (n=3), diarrhea (n=3), nausea (n=2), fatigue (n=2) and rash (n=2). Common treatment related adverse events included diarrhea (94.7%), nausea (78.9%), vomiting (71.1%), fatigue (52.6%), rash (39.5%), and elevated blood creating phosphokinase (36.8%). Two dose combinations satisfying criteria for the maximum tolerated dose (MTD) were identified: (1) sotrastaurin 300 mg and binimetinib 30 mg; and, (2) sotrastaurin 200 mg and binimetinib 45 mg. Exposure to both drugs in combination was consistent with single-agent data for either drug, indicating no PK interaction between sotrastaurin and binimetinib. Stable disease was observed in 60.5% of patients treated. No patient achieved a radiographic response per RECIST v1.1. Conclusions: Concurrent administration of sotrastaurin and binimetinib is feasible but associated with substantial gastrointestinal toxicity. Given the limited clinical activity achieved with this regimen, accrual to the phase II portion of the trial was not initiated.